THE DANGER OF PUTING ALL THE EGGS IN ONE BASKET. SOME CONCERNS REGARDING ROMANIA'S EXTERNAL TRADE - NEGREA Adrian (Annals of the University of Oradea: Economic Science, 2011)
Trade patterns across the globe vary in certain ways. For the EU27, the analyzed data suggests that approximately 70% of all Romania's imports, and the same amount of its exports, are intra-community oriented. The question that arises is what will happen to te Romania's external trade, if a crisis hits Europe? If countries like Germany, France, Italy, and United Kingdom are hit the hardest in this hypothetical European crisis, Romania will soon follow them. In order to decrease the impact of such possibility, it is necessary to tap new trade opportunities. For this purpose, first we have to analyze the present situation. Based on Eurostat, World Trade Organization, and the Romanian Statistics Institute data from 1999 to 2009, and on the works about trade creation (Balassa 1965, Jovanovic 2005, Molle 2006), the paper wants to point out the aspects of trade concentration in certain regions after the establishment of free trade agreements, and the danger posed by financial crises. This paper analyzes first the situation in the EU27, scanning each member state in order to see the degree of trade relations intra / extra EU. The data will be than compared to another set of analyzes of other four important regions, the Andean Community, ASEAN, MERCOSUR, and NAFTA, whose free trade agreements could support such of comparison with the EU trade relations. The paper follows the assumption that EU27 has the most integrated trade relations among all the analyzed regions. Based on this assumption and on statistical data that points out the percentage change of total imports and exports in the Romanian GDP, some conclusions will be drown out in order to establish some necessary measures to prevent a future crisis, measures that involve the political class, taping new trade opportunities such as Latin American countries, Middle Eastern countries, and South-East Asia, but not forgetting Russia, Romania's former main export partner, establishing clear objectives to future embassy personnel, and a more aggressive advertising campaign in the selected target markets conducted by national agencies.